Preparation and characterization of nano-silver/graphene oxide antibacterial skin dressing - Yang Liu; Liu Wang; Dawei Wen; Zhonghua Deng; Zhifang Wu; Sijin Li; Yongfeng Li (Scientific Reports)
Abstract This study aims to develop a composite hydrogel consisting of nano silver (Ag) and graphene oxide (GO) for use as a skin wound dressing. We prepared nanosilver/graphene oxide composite hydrogels by incorporating nanosilver and graphene oxide into kaolin-reinforced, gelatin-based hydrogels. Tests were conducted on the hydrogel’s water vapor permeability, mechanical properties, infrared warming performance and bacteriostatic properties under infrared light. The results indicated that kaolin enhanced the water vapor permeability and mechanical properties of the gelatin-based hydrogels. Moreover, the maximum fracture stress and strain of the hydrogel were elevated to 51.16 kPa and 1152.78% by GO, respectively. Furthermore, the modified Ag/GO hydrogels exhibited superior photothermal conversion and infrared bacteriostatic properties. This research offers valuable insights for the clinical repair of wounds and the design of new skin wound dressings, making these materials promising for such applications.